A novel SAD process: Match of anammox and denitrification. (1st April 2021) - Xu, Dongdong; Ying, Siying; Wang, Yihang; Zheng, Haoyang; Zhang, Meng; Li, Wenji; Chen, Wenda; Pan, Chao; Kang, Da; Zheng, Ping
Highlights: SAD system demonstrated efficient TN removal. Sustained COD release from SCS matched nitrate production in SAD system. AnAOB and DB grew separately while worked together to achieve efficient nitrogen removal. Abstract: Anammox biotechnology has been widely applied for its attractive advantages, but its application has been seriously limited due to the instinctive drawback of nitrate production. In this work, a novel Sequential Anammox and Denitrification (SAD) system was developed for the advanced nitrogen removal by using solid carbon source (SCS) and coupling anammox with denitrification. The long-term operation results demonstrated that the SAD system could remove the total nitrogen (TN) efficiently, with the effluent TN concentration of 1.4 ± 0.5 mg N/L, the TN removal efficiency (NRE) of 99.3 ± 0.2%, and the TN removal rate (NRR) of 1.7 ± 0.1 kg/(m 3 ·d). The determination results showed that SCS had a good property for sustained release of COD, with a dissolved organic yield (by COD) of 1.1 g-COD/g-rice. When the addition rate was set at 6 g-rice/7-days, the COD release rate of 0.9 kg-COD/(m 3 ·d) from SCS matched the nitrate production rate of 1.2 × 10 −1 kg-N/(m 3 ·d) from anammox with consumption ratio of 7.5. The analysis on the microbial community revealed that Candidatus _Brocadia and Denitratisoma were the dominant functional bacteria for anammox and denitrification, which contributed to about 92.7% and 6.6% of the total nitrogen removal, respectively. This work is helpful for the innovation and application of anammox-based technology. Graphical abstract: Image, graphical abstract